Towards a methodology to identify a talent by using psychological cognitive prototyping - Hammer, M. H. M. (Practice and Theory in Systems of Education, 2015)
Since education became an important aspect of society, teachers have a prelove for highly talented students. Especially young talented people relish profound attention of universities, firms, music ensembles, sports societies and artist groups. In higher education, students are encouraged to develop their unique strong point, named as talents. Around the globe, universities, institutes of higher and professional education provide students with programs for talent development and exploitation. Practitioners and educators complain on a regular basis that students rarely aware of what their talents are. It is experienced as difficult to identify them. This paper explores the possibility for mechanisms to identify, or recognize, a talent. Scholars and consultants developed many instrument on the development and exploitation of talents. But how can talents be identified? In this paper the fuzzy front end of talent recognition will be fostered. It is advocated that the psychological cognitive prototyping principles can be applied to identify the prototype of a talent.